2021
DOI: 10.3324/haematol.2021.280239
|View full text |Cite
|
Sign up to set email alerts
|

Kikuchi-Fujimoto disease associated with hemophagocytic lymphohistiocytosis following the BNT162b2 mRNA COVID-19 vaccination

Abstract: Not available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 12 publications
2
29
0
Order By: Relevance
“…To our knowledge, there are no data concerning the management of HLH in patients with thalassemia, and this is the first case report of a patient with HLH occurring after anti-SARS-CoV-2 booster dose. Other authors have recently described similar cases associated with the first doses of m-RNA or virus-vectored vaccines: some of them were successfully treated with corticosteroid therapy alone, obtaining a rapid remission of symptoms and improvement in blood counts [5][6][7][8]. Some recovered with support therapy alone [9], while others required etoposide or stronger combined therapies with steroids, IVIG and IL-1 receptor antagonists [8,[10][11][12].…”
Section: Discussionmentioning
confidence: 94%
“…To our knowledge, there are no data concerning the management of HLH in patients with thalassemia, and this is the first case report of a patient with HLH occurring after anti-SARS-CoV-2 booster dose. Other authors have recently described similar cases associated with the first doses of m-RNA or virus-vectored vaccines: some of them were successfully treated with corticosteroid therapy alone, obtaining a rapid remission of symptoms and improvement in blood counts [5][6][7][8]. Some recovered with support therapy alone [9], while others required etoposide or stronger combined therapies with steroids, IVIG and IL-1 receptor antagonists [8,[10][11][12].…”
Section: Discussionmentioning
confidence: 94%
“…Three of the patients developed KFD after receiving only the first dose of the vaccine, while the other developed KFD after the second dose. All of the patients had a good prognosis with resolution of symptoms [ 13 15 ] . There have been sporadic reports of cases of KFD following administration of the influenza vaccine, the human papilloma virus vaccine and the Japanese encephalitis vaccine [ 16 , 17 ] , although none of these are mRNA vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is a rare case reported in the literature, and only a few studies have reported HLH after receiving the COVID-19 vaccine. [5][6][7][9][10][11][12][13] It, therefore, it is important to document this condition in order to reiterate the occurrence of such events. Looking at the same scenario from a different angle, it has to be pointed out that rare vaccination events are important, as they help to identify and treat a small number of cases that react in this manner.…”
Section: Discussionmentioning
confidence: 99%